Perilaku Hidup Bersih dan Sehat sebagai Langkah Pencegahan Diare pada Siswa Sekolah Dasar - Syifa', Nailis; Wardana, Regita Pramesty Cahya; Wulandari, Putri Teky; Ariesta, Rossa; Rahmawati, Fina Eka; Ifada, Baiq Nurhaliza; Muhammad, Izbikavik (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
PHBS is a set of behaviors that are practiced based on awareness as an effort to be healthy and actively help the health of the surrounding environment. Clean and Healthy Behavior at an early age is important to maintain personal and environmental health. Early childhood is also susceptible to infectious diseases such as flu and diarrhea if they do not maintain personal and surrounding hygiene. Diarrheal disease is often considered a trivial matter but if it is not addressed it can result in quite serious matters. Therefore, we conducted community services which aims to provide students’ knowledge and understanding about Clean and Healthy Behavior and diarrheal diseases which often attack children at Muhammadiyah 1 Malang Elementary School students. The implementation method is carried out by counseling using power point media and videos. In the initial activity, a question-and-answer session was carried out, then giving educational material, showing educational videos, then evaluating it with a posttest.